Kalliapseudes (Mesokalliapseudes) macsweenyi, a new species of Kalliapseudidae (Crustacea: Tanaidacea: Apseudomorpha) from mangroves in Florida - Drumm, David T. (Zootaxa, 2003)
Kalliapseudes (Mesokalliapseudes) macsweenyi n. sp., is described from a tidal mangrove creek in Dania Beach, Florida. Of the four currently recognized species of Kalliapseudes (Mesokalliapseudes) Lang, 1956, K. macsweenyi most closely resembles K. crassus Menzies, 1953, a congener from the Pacific coast of Mexico. K. macsweenyi is distinguished from this species by having a rounded rostrum. It can be distinguished from the other three members of the subgenus by: the shape of the pereonites and the fixed finger of the female chelipedal propodus being approximately two-thirds the length of the dactylus. K. macsweenyi is unique in having a smooth and blunt triangular projection coming off the fourth peduncular antennal article.